2002
DOI: 10.1111/j.0014-3820.2002.tb00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Allele Frequency Shifts in Response to Climate Change and Physiological Consequences of Allozyme Variation in a Montane Insect

Abstract: Rapid changes in climate may impose strong selective pressures on organisms. Evolutionary responses to climate change have been observed in natural populations, yet no example has been documented for a metabolic enzyme locus. Furthermore, few studies have linked physiological responses to stress with allozyme genotypic variation. We quantified changes in allele frequency between 1988 and 1996 at three allozyme loci (isocitrate dehydrogenase, Idh; phosphoglucose isomerase, Pgi; and phosphoglucomutase, Pgm) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
73
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 65 publications
6
73
0
Order By: Relevance
“…In this species, PGI allele frequencies are found to vary along a thermal cline that follows latitude and altitude (Dahlhoff and Rank 2000;Rank and Dahlhoff 2002). Specific alleles are associated with cold vs. warm habitats and differ in both their biochemical performance and thermal stability (Dahlhoff and Rank 2000), suggestive of strong direction selection along the observed clines rather than widespread within population balancing selection.…”
Section: Pgi: Fitness Correlates In Arthropodsmentioning
confidence: 88%
See 4 more Smart Citations
“…In this species, PGI allele frequencies are found to vary along a thermal cline that follows latitude and altitude (Dahlhoff and Rank 2000;Rank and Dahlhoff 2002). Specific alleles are associated with cold vs. warm habitats and differ in both their biochemical performance and thermal stability (Dahlhoff and Rank 2000), suggestive of strong direction selection along the observed clines rather than widespread within population balancing selection.…”
Section: Pgi: Fitness Correlates In Arthropodsmentioning
confidence: 88%
“…An intriguing aspect of the work on C. aeneicollis is the correlation of heat shock protein (Hsp70) expression with different PGI genotypes (Dahlhoff and Rank 2000;Rank and Dahlhoff 2002). Detailed studies of heat vs. cold stress on adult fecundity, metabolic rate, running speed, and survival, as well as larval growth rate and survival, have found that PGI genotypes and Hsp70 interact with thermal exposure duration and temp, thermal history, and sex (Dahlhoff et al 2008;Dahlhoff and Rank 2000;McMillan et al 2005;Neargarder et al 2003;Rank et al 2007;Rank and Dahlhoff 2002).…”
Section: Pgi: Fitness Correlates In Arthropodsmentioning
confidence: 99%
See 3 more Smart Citations